2020
DOI: 10.1038/s41598-020-69381-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of GWAS and predictive breeding for European winter wheat’s grain protein content, grain starch content, and grain hardness

Abstract: Grain quality traits determine the classification of registered wheat ( Triticum aestivum L.) varieties. Although environmental factors and crop management practices exert a considerable influence on wheat quality traits, a significant proportion of the variance is attributed to the genetic factors. To identify the underlying genetic factors of wheat quality parameters viz., grain protein content (GPC), grain starch content (GSC), and grain hardness (GH), we evaluated 372 diverse Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 77 publications
5
50
1
Order By: Relevance
“…Protein contents in wheat grains depend on the chosen cultivar due to significant genetic variations [1], to contrasting fertilizer management and to environmental factors such as soil, rainfall and temperature, all affecting the nutrients uptake [2][3][4]. Furthermore, the grain protein content is negatively correlated with grain yield and grain starch content [5]. On average, wheat grain has a protein content of 8-13% [6], which is contributed by water/salt-soluble albumins and globulins (15-20%) and gluten proteins (80-85%), the latter serving as storage proteins and endowing wheat products with the desired viscoelastic and gustatory properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Protein contents in wheat grains depend on the chosen cultivar due to significant genetic variations [1], to contrasting fertilizer management and to environmental factors such as soil, rainfall and temperature, all affecting the nutrients uptake [2][3][4]. Furthermore, the grain protein content is negatively correlated with grain yield and grain starch content [5]. On average, wheat grain has a protein content of 8-13% [6], which is contributed by water/salt-soluble albumins and globulins (15-20%) and gluten proteins (80-85%), the latter serving as storage proteins and endowing wheat products with the desired viscoelastic and gustatory properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The world wheat trade is largely carried out based on hardness grades. Wheat hardness is a quantitative trait with classes ranging from soft to hard [1]. Two genes mainly determine hardness, puroindoline a and b (Pina and Pinb), which are located on the short arm of chromosome 5D (5DS) and form the molecular basis of wheat hardness [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the puroindoline genes, several studies have identified alleles that contribute to hardness; these were located on most of the 21 wheat chromosomes, but especially on chromosomes 1B, 2A, 4B, 5A, 5B, 5D, and 7D [1,[13][14][15]. Several researchers studied the hardness of plants grown under stress condition [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Protein turnover rates and ATP energy cost calculation. Protein synthesis rates and degradation rates were calculated using formulas as follows equation ( 4) equation (5) Where A is the protein starting abundance at the beginning of the labelling programme (7DPA).…”
Section: Gc-ms Data Acquisition and Processingmentioning
confidence: 99%
“…Although global wheat production continues to grow steadily, it is not sufficient to meet predicted demand, especially when the global population is projected to exceed 9 billion by 2050 requiring an increase of wheat production by about 70% 2,3 . To cope with such a challenge, researchers, breeders and wheat-processing industries have been working collaboratively to enhance yield while still maintaining grain-quality attributes such as grain protein content 4,5 .…”
Section: Introductionmentioning
confidence: 99%